(untitled) (Altre Modernità, 2022)
The initial outburst of the pandemic, in early 2020, forced China and the rest of the world into seclusion, anxiety, social alienation. In the Sinosphere, a human response to the aporia of isolation is the lyrical production, a prosperous literary activity through which the individual gives shape to a collective consciousness. The present paper examines a collection of Sinophone verses sprung from the Covid-19 threat and dismay, as a psychic necessity to re-organize the perception of the outer world. Specifically, it studies a body of fifty-two poems composed by twelve lyrical Sinophone voices, published in Chinese in a spring number of the respected literary journal Jintian 今天. This investigation primarily focuses on the cultural, aesthetic, and psychological value of a lyrical polyphony embodied by unchained Sinophone voices, which sing against the background of a common predicament. In parallel, it reads the collection as a collective memory and a cultural repository, engendered by a narrative projection of experience: to that end, it combines a narratological approach with the observation of certain lyrical features of a “poetics of distress”.